2017
DOI: 10.1103/physrevb.95.205306
|View full text |Cite
|
Sign up to set email alerts
|

Domain formation mechanism of the Si(110) “ 16×2 ” reconstruction

Abstract: The main factor that determines which of the two domains form upon reconstruction of the Si(110)"16 × 2" surface has been investigated. LEED and STM images showed that the domain orientation was independent of the heating current direction used to induce the Si(110)"16 × 2" reconstruction. Reciprocal-space lattice models of the reconstruction allowed for the correct identification of the domain orientations in the LEED images and confirm that the reconstruction is 2D-chiral. It is proposed that the domain orie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
3
7
0
Order By: Relevance
“…1 a. The observation of densely dotted lines along the and directions agrees very well with earlier studies 35 , 37 , 38 . In Fig.…”
Section: Resultssupporting
confidence: 90%
“…1 a. The observation of densely dotted lines along the and directions agrees very well with earlier studies 35 , 37 , 38 . In Fig.…”
Section: Resultssupporting
confidence: 90%
“…However, during the process of sample cleaning, not only zigzag chains extending in the direction but also those extending in the direction were also frequently dominant. Thus, the direction of the 16×2 reconstruction (or the direction in which zig-zag chains extend) was not related to the direction of current during sample heating, which is consistent with previous studies [12,22]. In the step area, two types of typical facets were observed: (17 15 1) and (15 17 1) [12,16] extending in the directions of and , respectively, which are indicated by dashed arrows in Figure 1.…”
Section: Resultssupporting
confidence: 89%
“…Particularly, the Si(110)-(16×2) reconstructed surface is considered to be an ideal 1D template [4,7,9]. Since this reconstructed surface is reported to be two dimensionally chiral, it has been the subject of many investigations, for example, in efforts to control the chirality for reliable production of nanowires and other nanostructures [7,[10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Yamada et al suggested that the electromigration induced the SD formation by comparing the current flow effect of two different orientation of rod-shaped Si(110) wafers [17]. They dominantly observed the SD structure on the wafer whose long side, i.e., the current flow direction, was [11 current did not affect the formation of SD [19], and Lewis et al reported that SD "16 × 2" could be formed on the vicinal surface with aligned monatomic steps running parallel to [11 _ 2] [20]. Since the present rectangular rods aligned almost perpendicular to the current flow direction and steps running parallel to [11 _ 2] are expected along the rectangle rod, the vicinity near the edge must be the reason for the present SD formation instead of the electromigration effect.…”
Section: Discussionmentioning
confidence: 99%